2016
DOI: 10.1016/j.jcyt.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Type II enhances chondrogenic differentiation in agarose-based modular microtissues

Abstract: Background Cell-based therapies have made an impact on the treatment of osteoarthritis, however the repair and regeneration of thick cartilage defects is an important and growing clinical problem. Next-generation therapies that combine cells with biomaterials may provide improved outcomes. We have developed modular microenvironments that mimic the composition of articular cartilage as a delivery system for consistently differentiated cells. Methods Human bone marrow-derived mesenchymal stem cells (MSC) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 82 publications
(79 reference statements)
3
32
0
Order By: Relevance
“…In total, we provide further evidence that ACPCs can be regarded as a promising alternative cell source for cartilage engineering. Moreover, taken together with previous studies [ 21 , 44 , 45 ], the results underscore the importance of the choice of an appropriate hydrogel for each cell type. Agarose appeared to be a suitable hydrogel for ACPCs, and thus may also be utilized in future studies when further investigating layered zonal constructs, while other types of gels may be considered for layers in which MSCs are applied.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In total, we provide further evidence that ACPCs can be regarded as a promising alternative cell source for cartilage engineering. Moreover, taken together with previous studies [ 21 , 44 , 45 ], the results underscore the importance of the choice of an appropriate hydrogel for each cell type. Agarose appeared to be a suitable hydrogel for ACPCs, and thus may also be utilized in future studies when further investigating layered zonal constructs, while other types of gels may be considered for layers in which MSCs are applied.…”
Section: Discussionsupporting
confidence: 70%
“…Agarose has been shown to support the native phenotype and morphology of chondrocytes [ 22 , 23 ], and appears to be a suitable environment for chondrocytes and their subpopulation, ACPCs. Taken as a whole, these results support that the selected hydrogel can largely influence the performance of the cells, and the choice of the hydrogel and cell type must be well matched to achieve the desired results [ 21 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 87%
“…It has however been noted to be adversely mechanically affected by the presence of cells: cells within agarose diminish the gel strength due to interference with the hydrogen bonding required for crosslinking and gelation (Shoichet et al, 1996). This limitation can be somewhat surmounted through combination with other polymers and proteins such as collagen, chitosan, and cellulose to increase cell affinity (Annamalai et al, 2016;Awadhiya et al, 2017). Research into the role of agarose composites has been explored for tissue engineering purposes for neural, vascular, bone, and pancreatic tissue (Bhatnagar et al, 2016;Zarrintaj et al, 2018).…”
Section: Agarosementioning
confidence: 99%
“…Collagen II, known to regulate chondrogenesis of mesenchymal stem cells, has been demonstrated to have the potential of facilitating osteogenesis and suppressing adipogenesis during early stage of mesenchymal stem cell differentiation [18]. Stegemann et al also revealed Collagen II to be a key factor in enhancing chondrogenic differentiation in agarose-based modular microtissues [19]. PCNA is widely accepted to be involved in distinct pathways of DNA postreplication repair [20].…”
Section: Discussionmentioning
confidence: 99%